Peningkatan Penggunaan Media Pembelajaran Bagi Guru-Guru di Yayasan Perguruan Dan Pembangunan Jauharotul Huda - Nurmala Dewi Qadarsih; Maimunah Maimunah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Teachers are still not optimally utilizing supporting media to improve the learning process in the classroom and outside the classroom, especially those using social learning network (SLN) technology. One SLN application that can be used by teachers is Edmodo. The purpose of this community service activity is to assist teachers in increasing the use of learning media, especially those related to SLN, so that learning is more interesting learning process does not only take place in the classroom. Community service activities carried out at the Foundation for Education and Development Jauharotul Huda. The method of implementation is by direct practicum and lecture. The results of these community service activities include: (1) the ability of teachers to operate Edmodo applications, (2) teachers can utilize information and communication technology in the learning process, and (3) develop teacher abilities in the use of instructional media.